Stereotyping representations and prejudice expression in Peru: The vision from poverty - Pancorbo, Gina (2011)
Stereotypes and prejudices towards different ethnic groups held by people from an extremely impoverished area in Callao, Peru were studied. A mixed methodology was designed, comprised of a survey study (n = 115) and four focus groups (n = 30). Results show the existence of specific stereotypes to represent groups of high (Whites) and low status (Andeans, Amazonians and Afro-Peruvians). Every assessed group was described through ambivalent stereotyping contents. Results show that white people were perceived as instrumentalist, corrupts and non-patriotic while low status groups were seen as low in instrumentalism but warmth and sympathetic. Comparing these results with Espinosa, Calderon, Guimac and Burga (2007), it becomes evident that stereotyping representations held by people of poor strata are structurally similar to those held by people of middle-class groups. However, prejudice toward high status groups’ members is stronger among poor respondents when compared with middle class respondents, because impoverished people are likely to consider members of high status groups as individuals with discriminatory and excluding behaviors against people of low status groups.